THE ROLE OF PHYTOTHERAPY IN OPTIMIZATION OF REHABILITATION AT A HEALTH RESORT IN PATIENTS WITH CHRONIC TONSILLITIS - E.I. Kondrat'eva; D.V. Sutovskaya; Yu.G. Grin'; V.G. Shmakov ("Paediatrician" Publishers LLC, 2010)
Authors present results of a treatment with complex of physical methods and phyto drug Tonsilgon N (Althaeae officinalis L., Chamomilla recutita, Equisetum arvense L., Juglans regia L., Achillea millefolium L., Quercus robur, Taraxacum officinale) of 35 children with chronic tonsillitis at a health resort. Clinical, immunological effectiveness and safety was estimated. Inclusion of the drug in treatment scheme resulted in decrease of morbidity with acute respiratory infections and rate of exacerbations of tonsillitis. Phyto drug has anti-inflammatory and immunomodulating activity manifested in increase of level of humoral factors in nasal secretion and cytoprotective effect related to positive changes in functional state of epithelium of nasal mucous membrane in children with chronic tonsillitis. Key words: children, chronic tonsillitis, rehabilitation, phytotherapy. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(2):58-63)